Delineation of Tundra Swan Cygnus c. columbianus populations in North America: geographic boundaries and interchange - Ely, Craig R.; Sladen, William J.L.; Wilson, Heather M.; Savage, Susan E.; Sowl, Kristine M.; Henry, Bill; Schwitters, Mike; Snowdon, James (Wildfowl, 2014)
North American Tundra Swans Cygnus c. columbianus are composed of two wellrecognised populations: an Eastern Population (EP) that breeds across northern Canada and north of the Brooks Range in Alaska, which migrates to the eastern seaboard of the United States, and a Western Population (WP) that breeds in coastal regions of Alaska south of the Brooks Range and migrates to western North America. We present results of a recent major ringing effort from across the breeding range in Alaska to provide a better definition of the geographic extent of the migratory divide in Alaska. We also reassess the staging and winter distributions of these populations based on locations of birds tracked using satellite transmitters, and recent recoveries and sightings of neck-collared birds. Summer sympatry of EP and WP Tundra Swans is very limited, and largely confined to a small area in northwest Alaska. Autumn migration pathways of EP and WP Tundra swans abut in southwest Saskatchewan, a region where migrating WP birds turn west, and EP birds deviate abruptly eastward. Overall, from 1989 to 2013 inclusive, 2.6% of recoveries or resightings reported to the USGS Bird Banding Laboratory were of birds that moved from the domain of the population in which they were initially captured to within the range of the other population; a proportion roughly comparable to the results of Limpert et al. (1991) for years before 1990. Of the 70 cross-boundary movements reported since 1989, 39% were of birds marked on breeding areas and 61% were of birds marked on wintering areas. Dispersing swans (i.e. those that made crossboundary movements) did not differ with respect to age or sex from those that did not move between populations. The Brooks Range in northern Alaska effectively separates the two populations within Alaska, but climate-induced changes in tundra breeding habitats and losses of wetlands on staging areas may alter the distribution for both of these populations.